2011
DOI: 10.7567/jjap.50.032301
|View full text |Cite
|
Sign up to set email alerts
|

A Cadmium-Free Cu2ZnSnS4/ZnO Hetrojunction Solar Cell Prepared by Practicable Processes

Abstract: A Cadmium-free Cu 2 ZnSnS 4 /ZnO hetrojunction solar cell with conversion efficiency of 4.29% has been obtained. The Cu 2 ZnSnS 4 absorber film was formed utilizing sulfurization of laminated metallic precursors, and the ZnO buffer layer was then deposited on it by ultrasonic spray pyrolysis. In comparison with a conventional Cu 2 ZnSnS 4 /CdS hetrojunction solar cell, the open circuit voltage as well as the relative quantum efficiency at the short-wavelength regions was increased. The in-plane homogeneity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Another interesting case of one dimensional growth by USP was observed by Htay et al [242,254,317,367,477] who reported micro-sized platelets, wires and tips of ZnO obtained at controlled conditions. Temperature of synthesis was found to dictate the morphology of the micro and submicronstructures that they obtained.…”
Section: One-dimensional Nanostructures From Usp: Nanowires Nanoribbmentioning
confidence: 91%
“…Another interesting case of one dimensional growth by USP was observed by Htay et al [242,254,317,367,477] who reported micro-sized platelets, wires and tips of ZnO obtained at controlled conditions. Temperature of synthesis was found to dictate the morphology of the micro and submicronstructures that they obtained.…”
Section: One-dimensional Nanostructures From Usp: Nanowires Nanoribbmentioning
confidence: 91%
“…Two types of precursors having a total thickness of 500 nm with different laminated layers (six and nine layers) were used in the experiments for investigating the influence of precursor structure. The details of the preparation of precursors and the sulfurization technique were reported previously [35,36]. Effects on the material properties due to the difference in the final Ge composition were investigated by utilizing analyses such as a scanning electron microscopy (FE-SEM, Hitachi, S-4100), an electron probe microanalysis (EPMA; Shimadzu EPMA-1610), an X-ray diffractometry (XRD, Rigaku, RINT-2200V/PCSV, Cu Kα ray; λ = 1.5418 Å with a Bragg-Brentano θ − 2θ geometry at 40 kV, 30 mA), a laser Raman spectrometry (COMET-3504, an excitation source of λ = 532 nm, a 1800 line mm −1 grating), an optical transmittance measurement (Spectrophotometer, Shimadzu UV-3100), a heat-probe conductivity measurement, and a four-probe resistivity measurement (Kyowa Riken, K89PS, tips gap: 1 mm).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The details of thin films preparation process and sulfurization technique were reported elsewhere. 5,34,35) The actual chemical compositions of the samples utilized in this experiment were described in Table I. An XDR (Rigaku RINT-2200V=PCSV, Cu Kα ray, λ = 1.5418 Å with a Bragg-Brentano θ-2θ geometry at 40 kV, 30 mA) was used to identify the crystalline quality of the thin films.…”
Section: Experimental Methodsmentioning
confidence: 99%